Li‐Breathing Air Batteries Catalyzed by MnNiFe/Laser‐Induced Graphene Catalysts. Issue 19 (5th August 2019) - Ren, Muqing; Zhang, Jibo; Fan, Mengmeng; Ajayan, Pulickel M.; Tour, James M.
Abstract: The development of efficient bifunctional catalysts for oxygen reduction and evolution reactions (ORR and OER) is important in the development of rechargeable metal–O2 (air) batteries. Here, a straightforward synthesis of highly efficient bifunctional OER/ORR catalysts MnNiFe/LIG (M111/LIG and M311/LIG where the numbers reflect the relative molar ratio of Mn, Ni, and Fe species) is presented through a facile re‐lasing method. The MnNiFe/LIG shows promising performance in Li–O2 and Li–air batteries without the presence of a redox mediator. The Li–O2 battery with M311/LIG catalysts is reliably discharged and charged for 150 cycles while the discharge potential slightly increases by 0.24 V. The Li‐breathing air battery with M311/LIG catalyst is stable during 350 cycles while the Li‐breathing air battery with M111/LIG catalyst is stable for ≈300 cycles. The function of the M111/LIG and M311/LIG catalysts in the Li–O2 batteries and the influence of the catalysts on the discharge and decomposition products are also investigated. This study promotes further development in carbon–metal oxide composite cathode catalysts for metal–air batteries and underscores the efficacy of laser‐induced graphene for electrode fabrications. Abstract : Here, two highly efficient bifunctional oxygen reduction reaction/oxygen evolution reaction (OER/ORR) catalysts are presented through a facile re‐lasing method. The MnNiFe/laser‐induced graphene (LIG) catalysts shows promising performance with >150 rechargeable cycles in Li–O2 and Li–air batteries. These findings point to efficient bifunctional catalysts for metal–O2 batteries and highlight the importance of tailoring the internal morphology for excellent cycling stability.